Application of Aspergillus Niger Bioremediation for the Treatment of Industrial Wastewater - Mamdwooh, Ali Esam; Alwan, Ibrahim Abed; Hosee, Yousif Nazzal (American Journal of Biology and Natural Sciences, 2026)
Bioremediation is a sector of biotechnology that utilizes living organisms, such as microalgae and fungi, to eliminate contaminants, pollutants, and toxins from soil, water, and various habitats. The current study aimed to evaluate some characteristics of industrial wastewater discharged through the collection of water samples, with one sample and three replicates. The physical, chemical, nutrient, and heavy metal properties were assessed, and fungal species were identified morphologically for treatment purposes. The evaluated physical properties included electrical conductivity and total dissolved solids. The chemical properties included total hardness, sodium ions, and potassium ions. The nutrients were chloride, sulfate, phosphate, nitrate, and active nitrite. The heavy metals were zinc, lead, iron, manganese, and aluminum. For physical properties, the removal rates for electrical conductivity reached 45.06%, while the total dissolved solids (TDS) rate was 43.93%. The efficiency of electrical conductivity was 31.89%, and for TDS, it was 58.66%. As for chemical properties of industrial wastewater treated by the treatment unit and Aspergillus niger fungus, they had varying percentages, with the highest removal rate of sodium ions being 89.81% and the lowest removal rate of calcium ions being 22.9%. The efficiency of sodium ions was 76%, and for total hardness, it was 54.46%, and the lowest was for potassium ions at 31.29%. While the nutrient was for nitrates (76.36%), the lowest was for phosphates (48.06%). The highest efficiency was for nitrate at 82.27%, and the lowest efficiency was for chloride at 51.36%. As for heavy metal, the highest treatment rates were achieved for manganese and lead at 99.77% and 99.66%, respectively. The remaining rates, from highest to lowest removal rate, were as follows: zinc, iron, and aluminum, at 89.2%, 85.92%, and 85.92%, respectively. The highest efficiency was for zinc at 99.78%, and the lowest efficiency was for aluminum at 45.83%.